(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
In the present comment, we point out some errors found in the above referenced paper. DOI: http://dx.doi.org/10.3329/jname.v9i1.10579 Journal of Naval Architecture and Marine Engineering 9(2012) T1-T2